Implementasi Kurikulum 2013 dalam Pembelajaran Fiqih di Madrasah Tsanawiyah Manba’ul Ulum Jatirejo Damarwulan Kepung Kediri - Haryadi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The curriculum is a very dynamic thing, therefore an educational institution should have innovation in developing its curriculum so that it becomes a trusted institution. This research was conducted to find out how to implement the 2013 curriculum in fiqh subjects at MTs Manba'ul Ulum Jatirejo Damarwulan Kepung Kediri. The results of the research conducted by the author can be concluded that the implementation of the 2013 curriculum in fiqh subjects at MA Manba'ul Ulum Jatirejo Kepung Kediri is good enough, but not optimal because there are some materials that require the use of the KTSP curriculum. As for the inhibiting factors in implementing the 2013 curriculum, namely difficulties in assessment, ineffectiveness and difficulty in evaluating.